Cone dystrophy phenotype associated with a frameshift mutation (M280fsX291) in the alpha-subunit of cone specific transducin (GNAT2). - Michaelides, M; Aligianis, I; Holder, G; Simunovic, M; Mollon, J; Maher, E; Hunt, D; Moore, A (2003)
AIM: To describe the phenotype of a three generation consanguineous Pakistani family containing six individuals with autosomal recessive cone dystrophy caused by mutation in GNAT2. METHODS: Five of the six affected individuals underwent an ophthalmological examination, electrodiagnostic testing, fundus photography, autofluorescence imaging, and detailed psychophysical testing. RESULTS: All five examined patients had a history of nystagmus from infancy, photophobia, defective colour vision, and poor visual acuity. The nystagmus in three of the individuals had lessened with time. Fundus examination revealed an abnormal foveal appearance, without frank atrophy or pigmentation. Electroretinography (ERG) revealed absent ISCEV cone flicker ERGs with some preservation of responses to short wavelength stimulation. Rod ERGs showed no definite abnormality, but maximal (mixed rod-cone) response a-wave amplitudes were mildly subnormal. Rudimentary residual colour vision was detected in three individuals. There is clinical evidence of progressive visual acuity reduction in two older individuals. CONCLUSION: Mutation in the alpha-subunit of cone specific transducin (GNAT2) is characterised by an infantile onset cone dystrophy. Some affected individuals may show deterioration of visual acuity with time.